Developing an Instrument for Assessing Self-Efficacy in Data Mining and Analysis - Wang, Yu-Min; Chiou, Chei-Chang; Wang, Wen-Chang; Chen, Chun-Jung (Frontiers in Psychology, 2021)
With the continuous progress and penetration of automated data collection technology, enterprises and organizations are facing the problem of information overload. The demand for expertise about data mining and analysis is increasing. The self-efficacy is a pivotal construct that has significant relationships with willingness and abilities to perform a particular task. Thus, the objective of this study is to develop an instrument for assessing self-efficacy in data mining and analysis. An initial measurement list was developed based on the skills and abilities about executing data mining and analysis, and expert recommendations. A useful sample of 103 university students completed the online survey questionnaire. A 19-item four-factor model was extracted by exploratory factor analysis. Using the partial least squares - structural equation modeling technique (PLS-SEM), the model was cross-examined. The instrument showed satisfactory reliability and validity. The proposed instrument will be of value to researchers and practitioners in evaluating an individual’s abilities and readiness in executing data mining and analysis.